2003
DOI: 10.1016/s0014-5793(03)00605-7
|View full text |Cite
|
Sign up to set email alerts
|

Down‐regulation of heat shock protein 27 in neuronal cells and non‐neuronal cells expressing mutant ataxin‐3

Abstract: Machado^Joseph disease (MJD)/spinocerebellar ataxia type 3 is an autosomal dominant spinocerebellar degeneration characterized by a wide range of clinical manifestations. Unstable CAG trinucleotide repeat expansion in the MJD gene has been identi¢ed as the pathologic mutation of MJD. In this study, human SK-N-SH neuroblastoma cells stably transfected with full-length MJD with 78 CAG repeats were established. Compared with the parental cells, cells expressing mutant ataxin-3 displayed normal morphology for over… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
17
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 42 publications
(21 citation statements)
references
References 40 publications
(44 reference statements)
3
17
0
Order By: Relevance
“…It was recently reported that Bcl-2 regulates an essential pool of mitochondrial GSH and that this regulation may depend on Bcl-2 directly interacting with GSH (Zimmermann et al, 2007). Consistently with these reports, we have previously shown that the levels of Bcl-2 (Tsai et al, 2004;Tien et al, 2008) and Hsp27 (Wen et al, 2003;Chang et al, 2005) in the cells harboring mutant ataxin-3 are significantly lower than those in cells harboring normal ataxin-3. Therefore, our observations could be explained, at least in part, by the decreased levels of Hsp27 and Bcl-2 in cells expressing expanded ataxin-3.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…It was recently reported that Bcl-2 regulates an essential pool of mitochondrial GSH and that this regulation may depend on Bcl-2 directly interacting with GSH (Zimmermann et al, 2007). Consistently with these reports, we have previously shown that the levels of Bcl-2 (Tsai et al, 2004;Tien et al, 2008) and Hsp27 (Wen et al, 2003;Chang et al, 2005) in the cells harboring mutant ataxin-3 are significantly lower than those in cells harboring normal ataxin-3. Therefore, our observations could be explained, at least in part, by the decreased levels of Hsp27 and Bcl-2 in cells expressing expanded ataxin-3.…”
Section: Discussionsupporting
confidence: 88%
“…Previous studies have demonstrated that cells stably expressing full-length mutant ataxin-3 do not undergo a rapid form of cell death under basal conditions and thus have likely undergone genetic or biochemical changes that allow them to cope with polyglutamine expansion (Wen et al, 2003;Tien et al, 2008). This observation is consistent with what is expected from the late onset of the disease.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…This protein minimizes infarct size, improves contractile function, and attenuates cardiac IR injury [13]. Reduced expression of HSP27 is correlated with poor overall survival [34].…”
Section: Discussionmentioning
confidence: 99%
“…Lymphoblastoid cells are frequently used as a model to study SCA (Wen et al 2003;Tsai et al 2005). In this study, we examined the length of the SCA8 repeats in ethnic Chinese Parkinson's disease (PD), Alzheimer's disease (AD) and atypical parkinsonism in Taiwan.…”
Section: Introductionmentioning
confidence: 99%